Forced vs. Intrinsic Wintertime Submonthly Variability of Sea Surface Temperature in the Midlatitude Western North Pacific - Wu, Yusheng; Zhou, Guidi; Wang, Guifen; Cheng, Xuhua (Frontiers in Marine Science, 2022)
The relative importance of wintertime forced and intrinsic SST variability in the Kuro-shio-Oyashio Extension (KOE) region on submonthly timescales (2-10 d and 10-30 d) is evaluated based on theoretical, observational, and modelling analysis. It is shown that the theoretical frame-work extended from the stochastic climate model has difficulties in representing SST variability on such short scales in the real ocean. Correlations of SST and heat flux, which is a well-accepted in-dicator for the direction of air-sea interaction derived from the theoretical framework, gives results that are hard to interpret. We then employ the GOTM oceanic single-column model to explicitly simulate the SST variability forced by atmospheric disturbances and compare it with observations. Results show that in the KOE region forced SST variability is responsible for a very small fraction of the total variability (< 10%) on the submonthly scales, indicating the dominance of intrinsic oceanic processes. Outside the KOE forced variability dominates. A set of sensitivity experiments are used to identify the key physical factors, namely vertical mixing in the upper ocean, wind stress forcing (mainly for outside KOE), and latent heat flux, the former two of which are not considered in the theoretical framework. The above results are robust against different levels of submonthly SST variability.